Role Of Lateral Incisors In Female - An Impact Towards Attractiveness Of Smile - FAIZ, NADHIRAH; MAITI, SUBHABRATA; NASIM, IFFAT; P, JESSY (The journal of contemporary issues in business and government, 2021)
Dental esthetics is a field of dentistry concerned especially with the appearance of dentition as achieved through its arrangement, form and color. The type of malocclusion, the degree of malocclusion, age, patients’ esthetic desires, practitioners’ style of treatment as well as gender predilection can influence the final esthetic treatment the patient will be subjected to. From functional demands, the patients of the current world, have shifted their demands to esthetics. Esthetics can be simply detected based on the position of lateral incisors. The aim of this study is to determine the prevalence of rotation, overlap and straightly positioned lateral incisors and its impact towards attractiveness of smile in female patients reporting to institutional setup in Chennai. A sample size of 500 patients’ information from a database of an institutional setup in Chennai was taken after reviewing 86,000 patients and a retrospective study was performed followed by data analysis using SPSS version 20.0 software. It can be said that the attractiveness of a smile depends upon the relation of the lateral incisors. P value associated with lateral incisor position and age of the sample size was found to be 0.361.